Is the return to education the same for everybody? - Douglas Webber (IZA World of Labor, 2014)
A postsecondary degree is often held up as the one sure path to financial success. But is that true regardless of institutional quality, discipline studied, or individual characteristics? Is a college degree always worth the cost? Students deciding whether to invest in college and what field to study may be making the most important financial decision of their lives. The return to education varies greatly by institutional quality, discipline, and individual characteristics. Estimating the returns for as many options as possible, and making that information as transparent as possible, are paramount in helping prospective students make the best decision.
Keywords: I21; I23; I24; J31; 330; education; human capital; earnings; college major